Anti-inflammatory and antioxidant activity correlation with total phenolic, flavonoids, and alkaloids of best-selling Indonesian jamu - Endah Puspitasari; Ari Satia Nugraha; Nuri Nuri; Ramadhan Bagus Cahyono; Putri Dwi Apriliani (Pharmaciana, 2026)
Oxidative stress and inflammation are closely linked pathological processes. Although non-steroidal anti-inflammatory drugs (NSAIDs) are effective, their use is associated with gastrointestinal, cardiovascular, and renal side effects, highlighting the need for safer alternatives. Jamu, an Indonesian traditional medicine, is widely used, yet scientific evidence supporting its efficacy and safety remains limited. The objective of this study was to investigate the anti-inflammatory and antioxidant activities of four different Indonesian jamu brands available for purchase on e-commerce platforms in Indonesia, and examine their correlation with the total phenolics, flavonoids, and alkaloids content in those jamu. The anti-inflammatory activity of jamu was assessed in vitro by evaluating its ability to stabilize red blood cell membranes and inhibit protein denaturation, using diclofenac sodium as a positive control. The antioxidant activity was evaluated using the 1-diphenyl-2-picrylhydrazyl (DPPH) assay, with ascorbic acid as the standard antioxidant. Total phenolics, flavonoids, and alkaloids contents were determined spectrophotometrically and expressed as gallic acid equivalents (GAE), rutin equivalents (RE), and berberine equivalents (BE) per gram of jamu extract, respectively. The correlations were evaluated based on multiple regression and Pearson correlation analysis using 99% confidence level. The aqueous extracts of Jamu A, B, C, and D were able to stabilize red blood cell membranes, inhibit protein denaturation, and exhibit free radical scavenging activity. Among the extracts, Jamu B demonstrated the lowest IC50 value, indicating the most effective anti-inflammatory and antioxidant properties followed by Jamu A, Jamu D, and Jamu C. These activities were significantly correlated with their total phenolics, flavonoids, and alkaloids content (p < 0.01).